Risk of stroke from new carotid artery occlusion in the asymptomatic carotid surgery trial-1 - den Hartog, A; Halliday, A; Hayter, E; Pan, H; Kong, X; Moll, F; de Borst, G (American Heart Association, 2013)
Background and Purpose — In the Asymptomatic Carotid Surgery Trial-1 (ACST-1), 3120 patients with tight asymptomatic carotid stenosis were randomly assigned to medical treatment alone or to carotid endarterectomy and appropriate medication. Successful carotid endarterectomy significantly reduced 10-year stroke risk in younger patients. This study was undertaken to determine the risk of new occlusion and stroke during trial follow-up. Methods — Patients with contralateral occlusion at trial entry (n=276) or incomplete duplex follow-up (n=137) were excluded. Risk of occlusion and stroke in patients with occlusion was estimated by Kaplan–Meier analysis. Cox proportional hazard regression models were used to determine risk factors for developing new occlusion and stroke. Results — Median follow-up in 2707 patients was 80.0 months (interquartile range, 52.0–115.0). New occlusions occurred in 197 patients (1.1% per annum) but were more likely to occur in arteries with tight stenosis and in unoperated patients. Overall risk of stroke was 7.6% (95% confidence interval [CI], 6.6–8.7) and 15.5% (95% CI, 13.6–17.4) at 5 and 10 years, respectively; for patients with new occlusion, this significantly increased to 17.0% (95% CI, 11.6–22.4) and 20.8% (95% CI, 14.1–26.2), respectively (P<0.001). Stroke was significantly more likely to occur in patients developing occlusion (hazard ratio, 1.78; 95% CI, 1.26–2.51) irrespective of allocated treatment. Conclusions — New occlusions were uncommon after carotid endarterectomy in ACST-1. During long-term follow-up, occlusion and stroke were commoner among patients with ≥70% stenosis, most of whom had not undergone carotid endarterectomy. Occlusion was an independent prognostic risk factor for occurrence of stroke.